A randomized controlled trial assessing the efficacy of a self-administered psycho-educational intervention for patients with cancer. Issue 4 (April 2019) - Körner, Annett; Roberts, Nicole; Steele, Russell J.; Brosseau, Danielle C.; Rosberger, Zeev
Highlights: Self-administered workbook, NuCare, shows promise as low-cost psychosocial intervention. NuCare leads to increased feelings of empowerment in patients with cancer. NuCare leads to higher quality of life in patients with cancer. Nucare reduces distress in patients with cancer. Abstract: Objective: Bibliotherapy refers to psychological self-help interventions that utilize treatment books to improve psychological well-being. Research supports bibliotherapy as an efficacious intervention for a variety of mental health problems. Yet, few studies have investigated bibliotherapy in psychosocial oncology. The objective of this randomized controlled trial was to examine the efficacy of the NuCare intervention, delivered as a self-directed workbook, for enhancing empowerment, coping, and quality of life and reducing distress in patients with cancer. Methods: Eighty-nine adult patients with cancer were randomized to receive the workbook for 6 weeks or the control condition, usual care. Participants completed questionnaires at baseline, 6 weeks post-baseline, and 10 weeks post-baseline. Results: The increase of empowerment (main outcome) and quality of life and the decrease of distress in the NuCare group from pre-intervention to follow-up assessment differed significantly from the respective difference scores in the control group. Conclusions: The self-administered NuCare workbook is a potentially cost-effective, minimal intervention addressing psychosocial needs of patients with cancer. Practice implications: Evidence-based bibliotherapy can empower patients and has the promise of reducing the burden on the healthcare system while enhancing the immediacy of psychosocial support.